Horticulture for a greener world - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (RON series., 2012)
"In this very special story of transcendent revelations and global repercussions, track the course of L. Ron Hubbard's horticultural discoveries. Told through articles and personal notes--here is a journey of discovery bearing upon all living things and the very essence of life itself."--